An Examination of Accounting Practices in the Pisuke Tradition of the Sasak Tribe - Susanthi, Septina; Sokarina, Ayudia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to reveal accounting practices in the pisuke tradition of the Sasak tribe in Mantang village. This study uses ethnography as an analytical method with an interpretive paradigm. Data collection was carried out through observation, interviews, and documentation. The results of the study indicate that the amount of pisuke is determined by a woman's social position such as family background, education level, and occupation. The concept of pisuke accounting describes income for women and obligations for men. The self-value of Sasak women in the pisuke tradition is recognized as an asset, capital, income, and burden. The pisuke tradition is not just a provision of material, but also a manifestation of social values ​​such as the values ​​of affection, respect, and family values. This finding can increase public insight that pisuke refers to financing wedding needs like its beginning. This tradition also shows how the Sasak people maintain cultural heritage by maintaining authenticity and preventing its extinction.